Visual Metaphor of Javanese Cartoon: The Interpretation of Cultural Socio-Politic in Goenawan Pranyotoâs Comic Cartoon Mbeling âAnde Ande Lumutâ (1951-2014) - Thalhah, Abdullah Ibnu (Harmonia: Journal of Arts Research and Education, 2016)
A comic cartoon is a communication media that is widely enjoyed and accepted by people. As a literary and journalistic work, the comic cartoon also captures the surrounding cultural situation. The modern and traditional cultural sign, fact and imagination, realist pattern and cartoon or caricature are used in a combination that seems contra versed (it is called double code discourse in postmodernism discourse), to show metaphor pattern relationship. The metaphor is applied through the transformation and play of the signs in the past and the future. They were spread, combined, and also transformed as a tool to show the creatorâs expression. In this research, it was found that there was a very close relationship between the use of metaphoric signs and Indonesiaâs social-politic situation in 1983. On one hand, Metaphor in comic cartoon Mbeling was a tool created to insinuate and criticize the corrupt and feudal Orde Baru authoritarian. It insinuated the violence involving the government officers in every aspect of the peopleâs life. On the other side, the comic cartoon also becomes the representation of contemporary Javanese culture that was open to other culture and acculturation.